PENERAPAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION DALAM MENINGKATKAN HASIL BELAJAR DI MTS MDIA TAQWA MAKASSAR - Azhar, Fitrah Maulani; Mustamin; Raehana, Syarifa; Akil, M; Azhar, Muh; Wahab, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the improvement of student learning outcomes through the application of the Team Assisted Individualization (TAI) learning model in the subject of Akidah Akhlak class VIII.1 MTs MDIA Taqwa Makassar. This research is motivated by the low learning outcomes of students caused by learning that is still centered on the teacher so that students are less active in participating in the learning process. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart model consisting of two cycles, where each cycle includes the stages of planning, implementation of actions, observation, and reflection. The research subjects were 31 students of class VIII.1 MTs MDIA Taqwa Makassar. Data collection techniques were carried out through observation, interviews, tests, and documentation. Data were analyzed using qualitative and quantitative descriptive analysis techniques. The results of the study indicate that the application of the Team Assisted Individualization learning model is able to improve student learning outcomes in the subject of Akidah Akhlak. In the pre-cycle stage, only 12 students (38.71%) achieved the Minimum Completion Criteria (KKM) with an average score of 68.04. After the Team Assisted Individualization learning model was implemented in cycle I, the number of students achieving the KKM increased to 21 students (67.74%) with an average score of 77.26. This increase occurred again in cycle II, with 29 students (93.55%) achieving the KKM with only 2 students (6.45%) remaining incomplete. In addition to improving learning outcomes, the implementation of the Team Assisted Individualization model also increased student activity, cooperation, courage to express opinions, and participation during the learning process. Thus, it can be concluded that the Team Assisted Individualization learning model is effective in improving student learning outcomes in the subject of Aqidah Akhlak, class VIII.1 MTs MDIA Taqwa Makassar.